Effects of Dynamic Surface Transformation on the Activity and Stability of Mixed Co-Mn Cubic Spinel Oxides in the Oxygen Evolution Reaction in Alkaline Media - He, Biao; Hosseini, Pouya; Escalera-López, Daniel; Schulwitz, Jonas; Rüdiger, Olaf; Hagemann, Ulrich; Heidelmann, Markus; DeBeer, Serena; Muhler, Martin; Cherevko, Serhiy; Tschulik, Kristina; Li, Tong (Advanced Energy Materials, 2024)
An atomic-scale understanding of how electrocatalyst surfaces reconstruct and transform during electrocatalytic reactions is essential for optimizing their activity and longevity. This is particularly important for the oxygen evolution reaction (OER), where dynamic and substantial structural and compositional changes occur during the reaction. Herein, a multimodal method is developed by combining X-ray fine structure absorption and photoemission spectroscopy, transmission electron microscopy, and atom probe tomography with electrochemical measurements to interrogate the temporal evolution of oxidation states, atom coordination, structure, and composition on Co2MnO4 and CoMn2O4 cubic spinel nanoparticle surfaces upon OER cycling in alkaline media. Co2MnO4 is activated at the onset of OER due to the formation of ≈2 nm Co-Mn oxyhydroxides with an optimal Co/Mn ratio of ≈3. As OER proceeds, Mn dissolution and redeposition occur for the CoMn oxyhydroxides, extending the OER stability of Co2MnO4. Such dynamic dissolution and redeposition are also observed for CoMn2O4, leading to the formation of less OER-active Mn-rich oxides on the nanoparticle surfaces. This study provides mechanistic insights into how dynamic surface reconstruction and transformation affect the activity and stability of mixed CoMn cubic spinels toward OER.
CRIS-Team Scopus Importer:2024-10-11
Keywords: atom probe tomography; cobalt spinels; dissolution; oxyhydroxides; water splitting